The Era of Genomics in Medicine: An Overview - Kasarla, Rajeswar Reddy; Rayudu, Lakshmi Kumari (Medical Journal of Eastern Nepal, 2026)
Genomics has become a cornerstone of modern biomedical research, transforming our understanding of the genetic basis of health and disease. The completion of the Human Genome Project marked the beginning of a transformative era in biomedical science, ushering in genomics as a central pillar of modern medicine. Over the past two decades, rapid advances in next-generation sequencing, bioinformatics, and systems biology have reshaped our understanding of disease pathogenesis, risk prediction, diagnosis, and therapeutic development. Advances in high-throughput sequencing technologies, bioinformatics, and data integration have enabled comprehensive analysis of genomes at unprecedented scale and resolution. This review provides an overview of the fundamental concepts, methodologies, and applications of genomics in clinical practice and biomedical research. We summarize key genomic technologies, including next-generation sequencing, genome-wide association studies, and functional genomics approaches, and discuss their roles in elucidating disease mechanisms, identifying genetic risk factors, and enabling precision medicine. The review also highlights emerging areas such as single-cell genomics, epigenomics, and multi-omics integration, which are further refining biological insights across diverse systems. In addition, we address current challenges related to data interpretation, ethical considerations, and clinical translation. By synthesizing recent developments and future directions, this article aims to provide a comprehensive resource for researchers and clinicians seeking to understand the impact of genomics on biomedical science and healthcare.